2023
DOI: 10.3390/cancers15082376
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Angiogenesis in the Era of Biliary Tract Cancer Immunotherapy: Biological Rationale, Clinical Implications, and Future Research Avenues

Abstract: Although biliary tract cancers are traditionally considered rare in Western countries, their incidence and mortality rates are rising worldwide. A better knowledge of the genomic landscape of these tumor types has broadened the number of molecular targeted therapies, including angiogenesis inhibitors. The role of immune checkpoint inhibitors (ICIs) could potentially change the first-line therapeutic approach, but monotherapy with ICIs has shown disappointing results in CCA. Several clinical trials are evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Prior studies have indicated that M2 macrophages are commonly linked to immune suppression, and the polarization state of these macrophages may influence the efficacy of immune suppressive signals. Therefore, we hypothesize that C4 cell clusters constitute the pivotal cell clusters in glioma patients who resist PD‐1 therapy 51,52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have indicated that M2 macrophages are commonly linked to immune suppression, and the polarization state of these macrophages may influence the efficacy of immune suppressive signals. Therefore, we hypothesize that C4 cell clusters constitute the pivotal cell clusters in glioma patients who resist PD‐1 therapy 51,52 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we hypothesize that C4 cell clusters constitute the pivotal cell clusters in glioma patients who resist PD-1 therapy. 51,52 We conducted differential analysis on the gene expression profiles in the C4 cell cluster between the Non and Res groups. We identified 147 upregulated genes and 3 downregulated genes.…”
Section: Ms4a4a Overexpression In Tams Correlates With Poor Response ...mentioning
confidence: 99%
“…14,[34][35][36] We observed several immune-oncology-related signatures that favored aoBTC versus eoBTC, namely, IFG, TIS, and differences in angiogenesis enrichment. [37][38][39][40] Despite the differences, the distribution of inflamed tumors was not significantly different in the two groups. Moreover, in assessing the TME with respect to immune cell infiltration, no significant differences could be identified.…”
Section: Discussionmentioning
confidence: 83%
“…TAMs directly affect regulatory T-cells, impeding tumor immunity while accelerating angiogenesis and the degeneration of the extracellular matrix. These actions promote the development and progression of tumors ( 43 , 44 ). As a result, TAMs can be considered an indicator of a high cancer burden.…”
Section: Discussionmentioning
confidence: 99%